Improving Knowledge of Sports Games Training Programs for Junior High School Physical Education Teachers in the Purwokerto Region - Didik Rilastiyo Budi; Topo Suhartoyo (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The preparation of training programs for sports achievement coaching activities in schools, mainly Junior High Schools (SMP) through the Sports Extracurricular program, is an essential factor that coaches and mentor teachers must pay attention to so that the coaching process can run well. The purpose of this Community Service (PKM) activity is to increase the knowledge and skills of coaches and sports extracurricular coaches in preparing training programs. The activity method used is through training, mentoring and activity evaluation. The training was attended by 20 sports extracurricular coaches and teachers in SMP throughout Purwokerto. The training and mentoring results showed that in the initial test, it was found that most of the participants did not understand the preparation of an exercise program so that they were not able to compile an exercise program properly. In contrast, the final test carried out at the end of the activity showed an increase in the participants' understanding of a sports training program's preparation. The participants training participants can compile a game sports training program that will be implemented in school extracurricular activities.